Pengaruh Customer Online Reviews, Flash Sale dan Tagline Gratis Ongkir terhadap Pembelian Impulsif pada Aplikasi Tik Tok - Ali Zaki Nur Romadhoni; Dian Ayu Liana Dewi (eCo-Fin, 2025)
Impulsive buying is an act of purchasing done suddenly without any consideration, which can lead to regret. The aim of this study is to demonstrate how flash deals, customer online reviews, and the phrase "free shipping" affect impulsive purchases made by Rembang Regency TikTok users.  Customers in Rembang Regency who are between the ages of 18 and 40 who have used the Tik Tok app to make purchases online make up the research population.  Purposive sampling was the method of sampling that was employed.  Using SPSS 24, the data analysis method included multiple linear regression analysis. The study's findings demonstrate that while flash sales have a significant positive impact on impulsive purchasing, customer online reviews and the tagline "free shipping" have a positive but negligible effect.  Only 57.5% of impulsive purchases can be explained by the three independent factors in this study, according to the determination test results; the remaining 42.5% can be explained by variables not included in this study.